Evaluasi Program Pendidikan Inklusif Pada Satuan Pendidikan Sekolah Dasar Di Kecamatan Cibinong Kabupaten Bogor Tahun 2023 - ine Ulfah Safitri; Leo Agustino (Epistemik Press, 2026)
This research focuses on inclusive education programs in Cibinong District. The problems that occur and are studied by researchers are that there are no special assistant teachers available at Cibinong District Elementary Schools, State Elementary Schools appointed to implement inclusive education, some of them have not implemented accommodation or modified curricula and there are no adequate facilities and infrastructure available for teaching and learning activities for ABK in State Elementary Schools from both the Central Government and the Department. Bogor Regency Education. This research uses qualitative methods by analyzing results, interviews, observations, documentation and document studies. The results of this research show that based on the program evaluation presented by Program Evaluation (2023), the inclusive education program has not fully run well due to various factors. Overall, this program has not been able to run optimally in providing services to crew members.